ECONOMIC KNOWLEDGE IN SOCIAL-PHILOSOPHICAL CONTEXT - Синяков, С. В.; Сластенко, Е. Ф. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The authors analyze the dependence of cognitive means on peculiarities of the subject of research in economics. The influence of philosophy, sociology, culturology and other sciences on the process of the study of economic phenomena and processes is revealed. The impact of modified ideas of the nature of economic objects on formation of the system economic knowledge is proved.